2010
DOI: 10.1084/jem.20101138
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-A4–semaphorin 3A signaling is required for Toll-like receptor– and sepsis-induced cytokine storm

Abstract: Plexin-A4 activity is essential for Toll-like receptor–induced signaling, cytokine production, and inflammation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 41 publications
3
83
1
Order By: Relevance
“…29 This observation is supported by studies in which it was observed that sema3A signaling is impaired in mice lacking functional plexin-A4 or plexin-A1 receptors. [31][32][33][34] In another study it was also found that plexin-A4 receptors transduce sema3A guidance signals that affect the organization of the cytoskeleton at growth cones. Interestingly, in this study it was fond that plexin-A3 also transduces sema3A signals.…”
Section: Plexinsmentioning
confidence: 94%
“…29 This observation is supported by studies in which it was observed that sema3A signaling is impaired in mice lacking functional plexin-A4 or plexin-A1 receptors. [31][32][33][34] In another study it was also found that plexin-A4 receptors transduce sema3A guidance signals that affect the organization of the cytoskeleton at growth cones. Interestingly, in this study it was fond that plexin-A3 also transduces sema3A signals.…”
Section: Plexinsmentioning
confidence: 94%
“…Mouse kidney proximal tubular epithelial cells (TKPTS) were grown to confluence using advanced DMEM/F-12 medium containing 5% serum in a six-well plate. On the day of treatment, serum-free advanced DMEM/F-12 medium was added, and cells were treated with 50 ng of LPS with 100 ng/ml of sema3A or vehicle for a period of 4 h. Sema3A dose was based on previous studies in macrophages (34). Supernatant and RNA were isolated at the end of the experiment for quantification of cytokines and chemokine expression.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggest that sema3A contributes to sepsis-induced cytokine storm and TLR signaling (34). This suggested that sema3A might cooperate with TLR4 signaling to induce inflammation and kidney damage in AKI.…”
Section: Sema3a Inactivation Blunts Inflammation and Apoptosis In Resmentioning
confidence: 95%
See 1 more Smart Citation
“…Following acute kidney injury induced by transient ischemia or by cisplatin, Sema3A protein expression is upregulated in distal and collecting tubules [17,18]. Under these pathophysiological conditions, infiltrating immune cells are likely to serve as an additional source of Sema3A in the kidney [18,19]. The functional role of Sema3A in ischemia/reperfusion injury in vivo has been assessed by both pharmacological as well as genetic approaches employing mice, which carry a loss-of-function mutation in the Sema3A gene.…”
Section: Semaphorins and Plexins In Acute Kidney Injurymentioning
confidence: 99%